The characteristics of cancerous patients infected with COVID-19 in hospital setting - Sadeghi, Amir; Dooghaie Moghadam, Arash; Eslami , Pegah; Pirsalehi, Ali; Shojaee, Sajad; Sanadgol, Ghazal; Jalilian Khave , Laya; Vahidi, Mohammad; Asadzadeh Aghdaei , Hamid; Nazemalhosseini Mojarad, Ehsan (Acta Biomedica Atenei Parmensis, 2020)
Introduction: Recently, Covid 19 as a fatal virus has been known as the cause of the pandemic. Different number of the mortality rate in various societies have been reported. However, it seems the underlying comorbidities increase the risk of mortality and the severity of presentation. In this study we evaluated the pattern of presentation of COVID-19 among cancerous patients in terms of severity.Method: between 20th February to 22nd April of 2020, among 214 hospitalized patients because of COVID-19. 41 patients revealed the cancer as a synchronous comorbidity. These patients based on the severity of COVID-19 infection presentation were divided to mild and severe groups. Then, the demographic characteristics, manifestation and laboratory data between these groups were compared.Result: about 19 (46.34%) of 41 cases were categorized as severe forms of COVID-19 with malignancy. The mean age of severe groups was significantly higher (P=0.00). Dyspnea (48.78%), cough (46.34%) and myalgia (24.39%) were the most common clinical features among cancerous patients with COVID-19.  diarrhea and nearly cough caused significant effects on severe form of presentation of COVID-19 infection (P=0.05, P=0.06, respectively). Hematological cancers were the most frequent types of cancer among these patients (46.34%). White Blood Cell counts were significantly lower in severe groups (P=0.03, P=.0.06, respectively). C-reactive protein is another item that nearly significantly was higher in severe groups of cancerous patients (P=0.06).Conclusion: The elderly age, the positive chemotherapy history, diarrhea, cough, declined WBC, PLT and elevated CRP correlated with a severe form of this infection in malignant cases.